2016
DOI: 10.4238/gmr.15027487
|View full text |Cite
|
Sign up to set email alerts
|

Gender and ethnicity modify the association between the CYP1A2 rs762551 polymorphism and habitual coffee intake: evidence from a meta-analysis

Abstract: ABSTRACT. The association between the single nucleotide polymorphism rs762551 in the cytochrome P450 family 1, subfamily A2 gene (CYP1A2) and caffeine consumption remains controversial. We conducted a metaanalysis to clarify this potential association. Twelve studies were selected from articles retrieved from the and Google Scholar databases, and the data were analyzed to determine the odds ratio (OR) of genotypes AA (conferring fast caffeine metabolism) vs AC + CC (conferring slow caffeine metabolism). Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…The analysis showed an association between the AA genotype and coffee consumption [OR = 1.13, 95%, CI = 1.03-1.24, P = 0.06]. This association was found in men, individuals younger than 59 years, and Caucasians, but not in females, individuals older than 59 years, and Asians [206].…”
Section: Metabolism and Distributionmentioning
confidence: 96%
“…The analysis showed an association between the AA genotype and coffee consumption [OR = 1.13, 95%, CI = 1.03-1.24, P = 0.06]. This association was found in men, individuals younger than 59 years, and Caucasians, but not in females, individuals older than 59 years, and Asians [206].…”
Section: Metabolism and Distributionmentioning
confidence: 96%
“…This is the first study pointing out the weak association between the fast caffeine metabolizer profile and coffee intake in the Asian population, as well as the age-and sex-related variation. These specificities need to be further explored (Denden et al, 2016).…”
mentioning
confidence: 99%
“…The ratio of caffeine and its metabolites in plasma and urine after caffeine consumption is known to affect rs762551 polymorphism. Specifically, individuals with genotypes AA, AC, and CC are known as extensive, intermediate, and poor metabolizers of caffeine, respectively [26][27][28][29]. Although we found that genotype CC had a relatively low degree of change in S90m…”
Section: Discussionmentioning
confidence: 51%
“…There are various polymorphisms in CYP1A2, and SNPs rs762551 and rs2472297 are known to affect the efficiency of caffeine metabolism. Specifically, individuals with rs762551 alleles AA, AC, and CC are characterized as extensive, intermediate, and poor metabolizers of caffeine, respectively [26][27][28].…”
Section: Introductionmentioning
confidence: 99%